ANALYSIS OF STUDENTS’ LEARNING DIFFICULTY IN ENGLISH LESSON AT MTS NURUL FALAH CIMAHI - Ema Rachmawati; Mia Selvia Rachmawati (IKIP Siliwangi, 2018)
This article focuses on the analysis to find out the difficulties of students MTs in English Learning. The sample of this study is used for some students from 36 students in VII grade of MTs Nurul Falah Cimahi. This method uses Qualitative approach in the analysis. The result is that students difficulties, in learning English 85% not appropriate. Some expert suggest external factor and internal factor that be affect students learning difficulties to learning difficulties. The author only focus on one factor that is external factor. External factors are : School factors, Family factors, and Environmental factors. The result of the analysis, the external factors that most affect the difficulties tudent learn English in MTs. Nurul Falah is the School and Family factors